End of sentence [videorecording (DVD)] - Armbruster, Michael; Hawkes, John, 1959-; Lerman, Logan, 1992-; Bolger, Sarah, 1991-; Irvine, Andrea; Ólafur Darri Ólafsson (Gravitas Ventures, 2020)
After Sean is released from prison, he reluctantly embarks on a journey with his alienated father to spread his mother's ashes in her native Ireland.